TUNGSTEN-BEARING MINERAL OCCURRENCES OF BATUBESI TIN SKARN DEPOSITS - Sugiharto, Mochamad Slamet (Bulletin of Geology, 2024)
Batubesi tin skarn deposit is a part of Southeast Asian Tin Belt which is the world class resources of primary tin deposit, and is related in time and space to ilmenite series granitic intrusion. It has been known that Batubesi tin skarn deposit was categorized as Fe-Sn skarn deposit and cassiterite was still the main ore mineral. However, there is no previous study mentioned other potential economic mineral instead of Fe and Sn-bearing minerals. Tikus greisen deposit in Belitung Island is known as one of tin deposit containing tungsten (W). The aim of this study is to determine the presence of tungsten (W) in the Batubesi tin skarn deposit and its tungsten-bearing mineral. X-Ray Fluorescence (XRF) analysisboth portable and laboratory, X-Ray Diffraction (XRD), and Scanning Electron Microscope (SEM/EDS) analysis have been carried out on the current drillhole data to identify tungsten occurrences. Based on XRF analysis, there was anomaly of tungsten but the distribution of tungsten-bearing mineral is found only in certain part and not correlated as the whole with Sn bearing skarn body. It is confirmed from the SEM/EDS elemental mapping. The result of XRD analysis indicated that tungsten-bearing minerals in the Batubesi tin skarn deposit found as scheelite and the composition is more dominant compare to wolframite. Key words: Batubesi, skarn, tin, tungsten, ore